SHAPING LEARNER CONTRIBUTIONS IN THE EFL LANGUAGE CLASSROOM: A CONVERSATION ANALYTIC PERSPECTIVE - Cancino, Marco (Lenguas Modernas, 2018)
The present study sought to demonstrate the importance that the shaping of learner contributions has in the provision of opportunities for participation and learning in the EFL classroom. A particular set of interactional features that can shape learners’ utterances were examined: scaffolding, requests for clarification and confirmation checks. These features have been found to promote language participation and learning from a classroom discourse perspective (Walsh, 2002; Walsh and Li, 2013; Can Daşkın, 2014). The study was also informed by the socio-cultural concept of learning as a social affair that is achieved through participation (Lantolf, 2000; Donato, 2000; Mondada & Pekarek, 2004). A Conversation Analysis (CA) methodology was used to analyse two extracts collected in EFL classrooms at a language institute in Santiago, Chile. Findings suggested that when teachers shape their learners’ contributions by means of scaffolding, clarification requests and confirmation checks in a pedagogical environment that promotes conversation, participation and learning will likely be enhanced.